A placebo-controlled blind trial of cyclosporin-A in prevention of corneal graft rejection in rabbits. Issue 5 (May 1982) - Bell, T A; Easty, D L; McCullagh, K G
Abstract : Cyclosporin-A (CyA) administered to rabbits intramuscularly in a dose of 25 mg/kg/day for 14 days following interlamellar corneal grafting had a significant effect in preventing rejection of the corneal graft (p less than 0.05), and the benefit was maintained. Rejection was attended by an initial mild inflammatory reaction and followed by a protracted intense response involving a variety of cell types, with subsequent loss of epithelium. endothelium and keratocytes, and the development of areas of stromal necrosis. CyA suppressed this rejection response.